2017
DOI: 10.1016/j.compedu.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Copying@Scale: Using Harvesting Accounts for Collecting Correct Answers in a MOOC

Abstract: This paper presents a detailed study of a form of academic dishonesty that involves the use of multiple accounts for harvesting solutions in a Massive Open Online Course (MOOC). It is termed CAMEO -Copying Answers using Multiple Existence Online. A person using CAMEO sets up one or more harvesting accounts for collecting correct answers; these are then submitted in the user's master account for credit. The study has three main goals: Determining the prevalence of CAMEO, studying its detailed characteristics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 28 publications
2
86
0
Order By: Relevance
“…The data in fake learners logs is largely an artifact with respect to explaining their performance. As was pointed out in [4], this can bias LA and EDM results. For example, fake learners typically make minimal interaction with the learning materials, yet show high success; this can lead to false conclusions regarding the effectiveness of different learning paths or the pedagogic efficacy of course materials.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The data in fake learners logs is largely an artifact with respect to explaining their performance. As was pointed out in [4], this can bias LA and EDM results. For example, fake learners typically make minimal interaction with the learning materials, yet show high success; this can lead to false conclusions regarding the effectiveness of different learning paths or the pedagogic efficacy of course materials.…”
Section: Introductionmentioning
confidence: 89%
“…Fake Learners. However, several studies revealed that there are a considerable amount of users who use cynical means to succeed in the courses, such as Cheating Using Multiple Accounts [3,18,4,15], or unauthorized collaboration [19]. Such users break the 'genuine learning behavior' assumption, thus we refer to them as fake learners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive modeling research evaluated in this work is situated in the context of a much larger and broader body of MOOC-related research. Prior research on MOOCs has covered a broad variety of topics, including changes in learner discourse over time (Dowell et al, 2017), interventions to improve student completion (Kizilcec and Cohen, 2017), demographics and participation rates and the relationship to course activity (Guo and Reinecke, 2014), and student plagiarism and academic honesty issues (Alexandron et al, 2017). Additionally, the researchers addressing this topic, both in the predictive context and more broadly, come from a wide variety of academic perspectives, including learning theory, social and experimental psychology, computer science, statistics, economics, design, and linguistics.…”
Section: Relation To Other Mooc Researchmentioning
confidence: 99%
“…Visual tools (e.g., emoticons, colour, visual imagery and similar, see Dixson et al, 2016) may support self-reflection, and also engagement with, feedback on activities (see also Govaerts et al, 2010). HCI experts may be able to implement notifications (e.g., D'Antoni et al, 2015) and actual real-time detection methods to track attempts at manipulation (e.g., in online tests; see also Alexandron et al, 2017). Sharing such information with online students may increase their utilisation of feedback and foster actual learning, while reducing attempts to game the online system.…”
Section: Feedback: From Generation To Utilisationmentioning
confidence: 99%